Effect of Recruitment Maneuvers on Oxygen Saturation, End Tidal Carbon Dioxide and Lung Mechanics in Pressure Control Ventilation Versus Volume Control Ventilation for Patient Undergoing Laparoscopic Sleeve Gastrectomy - Al Saad, Sabah N. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Atelectasis occurs regularly after induction of general anesthesia in bariatric surgery, persists postoperatively, and may contribute to significant postoperative morbidity. Intraoperative recruitment maneuver improve lung ventilation, oxygenation and lung mechanics.Objectives: The aim of this study was to compare the effects of recruitment maneuver on oxygen saturation, end tidal carbon dioxide and lung mechanics in two Groups; the volume control group and pressure control group with fixed level of PEEP.Patient and Method:  Forty patients, BMI >35 kg/ m2, who have no major obstructive or restrictive respiratory disorders where allocated in two groups (volume group and pressure group). In both groups we tested the effect of recruitment maneuver on SpO2, ETCO2 and lung mechanics  (The volume group of 20 patients and the pressure group of 20 patients).Results: We found that alveolar recruitment effectively decreased Intraoperative EtCO2  in pressure group ( P.value 0.05 ) for volume group and increase Intraoperative SpO2in BOTH groups ( P.value < 0.05) with more effect seen in pressure group. BUT, soon after extubation SpO2 decreases again and P.value  was >0.05 for both groups.Also we found that pulmonary mechanics (PIP, EXPvt) were significantly improved after recruitment (BOTH P.value < 0.05).Conclusions:  our data suggest that the use of alveolar recruitment maneuver may be an effective mode of improving intraoperative oxygenation in morbidly obese patients. Our results showed that the effect is to be short lived and end after extubation. with significant improvement in lung mechanics.